Orienting faculty about medical student's perception: An essential yet missing area in curriculum development in new INI's (Institute of National Importance) - Neeti Rustagi; Ranabir Pal (Al Ameen Medical College, 2018)
Introduction: Investigating educational environments in a newly established medical institution is imperative to promote effective learning and facilitate delivery of quality medical education. The current study assessed the student's perception and faculty feedback regarding educational environment in a newly established institute of national importance in India. Methodology: The current study was undertaken among two consecutive batches of students in three phases; Dundee Ready Educational Environment Measure (DREEM) questionnaire was administered to all the volunteering students followed by small group discussions of students. A faculty orientation session was conducted to invite their feedback on student's shared perception. Results: Response rate of 82.7% and high reliability coefficient (0.893) for DREEM's questionnaire was observed. Mean total DREEM score was 125.7±19.7. Mean scores of most of the items scored between 2 and 3. Students reported teaching learning activities to be interesting and teachers to be interactive with overall emphasis on practical learning. Strict discipline, continuous stress of academics and fewer opportunities to engage in extracurricular activities were identified as problem areas. The reported problem of students was acknowledged by faculty as essential areas to improve upon with advancing years. Need of strict discipline was considered essential by many faculty members. Conclusions: Defining of educational environment in a newly established institute requires orientation of course planner and faculty members about student's expectations. Planned academic schedule need to incorporate extra-curricular activities and time for self - study by students to enhance positive educational environment.